Assessing the role of sustainability competencies in enhancing psychological first aid effectiveness for disaster responders in Fiji - Nair, Malini; Meirmanov, Serik (Frontiers in Public Health, 2024)
Background Psychological first aid (PFA) is essential for mental health and wellbeing after traumatic events. Integrating competency-based outcomes is crucial with the increasing demand for effective psychological first-aid interventions. This study examines the correlation between sustainability competencies and PFA principles within Fiji's disaster responder's context. Method The research was guided by a theoretical framework based on a comprehensive review of sustainability competencies and PFA principles. A cross-sectional survey assessed the importance of sustainability competencies in disaster responders to deliver PFA effectively. The survey used a stratified random sampling method to get diverse PFA-trained participants (66%) and non-PFA trained (34%), aiming to understand how these competencies can impact PFA success in various disaster situations. The survey, encompassing various domains of disaster response and a diverse range of respondents age, gender, and years of experience, employed the Likert scale to assess the importance of competencies such as integrated problem-solving, strategic, systems thinking, self-awareness, normative, collaboration, anticipatory, and critical thinking. Results The study involved 49 PFA-trained participants (55% female, 45% male) and 15 non-PFA-trained participants (53% female, 46% male), excluding 10 responses from the latter group due to ambiguous answers to critical questions. The correlation between age, experience, and the valuation of professional competencies among disaster responders indicates that disaster responders, with extensive experience and PFA training, rated competencies as “important,” reflecting a perspective shaped by long-term career development and practical experiences. Equally, younger and early career responders emphasize competencies as “very important,” indicating an initial recognition of their significance. The appraisal patterns across different age groups, especially among those with PFA training, suggest a tendency to moderate assessments of competency importance with increasing experience. Statistical analysis, including mean, median, standard deviation, and variance, provided a detailed understanding of the data, underscoring competencies like self-awareness in both data sets and integrated problem-solving and collaboration within PFA-trained responders as the key for effective PFA interventions. Conclusion The study underlines the critical need to integrate sustainability competencies into the PFA curriculum in Fiji's unique sociocultural context. This interplay between age, experience, and competency assessment stresses the diverse factors influencing perceptions in the disaster response field beyond experience alone. The results show that sustainability competencies are the ultimate to the effectiveness of PFA measurement and interventions. The research lays the foundation for future studies to develop validated tools for assessing sustainable competencies in different cultural contexts, thereby improving the effectiveness of PFA in disaster management. Integrating these competencies into PFA training could significantly strengthen PFA intervention and competency-based evaluation.